Fighting Fake News A Generational Approach - Loos, Eugène; Ivan, Loredana (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book focuses on how different generations perceive fake news, including young and middle-age groups of people, multiple age groups, university students and adults in general, elementary students, children, and adolescents. It provides insights into the different methodologies available with which to research fake news from a generational perspective.